Blood Profile of Rabbits Infected with Eimeria magna - Hana, A; Salasia, SIO; Mangkoewidjojo, S; Kusindarto, DL (ANIMAL PRODUCTION, 2011)
Abstract. The research aimed at determining the blood profile of local rabbits infected with different dose of Eimeria magna oocysts. This research used 45 male rabbits with the age of 4 month old, range from 1.5 to 1.8 kg, clinically healthy and free from coccidiosis. The rabbits were randomly divided into 3 groups, group I as control (K-0) was given 1.0 ml distilled water/rabbit orally, group II (K-10) was infected with single dose of 10x106 oocysts of E. magna/rabbit orally, and group III (K-20) was infected with single dose of 20x106 oocysts of E. magna/rabbit orally. After infection, rabbits were examined for clinical signs, body weight and temperature daily for five days. Blood samples were drawn from the vena marginalis to examine the number of erythrocytes, hemoglobine, packed cell volume (PCV), leukocytes and its deferent, total protein plasma (TPP) and fibrinogen, activities of alkaline phosphatase (ALP), alanine amino transferase (ALT), and aspartat aminotransferase (AST). The data were statistically analyzed by two-way anova using factorial design. The results of this research showed that the infection of E. magna in rabbits caused fever and weight loss, accompanied by normochromic microcytic anemia (at doses of 10x106 oocysts), macrocytic normochromic (at doses of 20x106 oocysts), leukocytosis, lymphocytosis, hiperfibrinogenemia, and increased of ALP activity. There were correlations between clinical symptoms and blood profile of rabbits infected with E. magna for five days. The higher the dose and the longer the infection of E. magna in rabbits caused weight loss, increased body temperature, MCV (microcytic to macrocytic), leukocyte, fibrinogen and ALP activity. These findings were useful to have a better understanding of pathophysiology of E. magna infection inÂ  rabbits.Key Words: Eimeria magna, oocyst, rabbit, blood profileA Hana et al/Animal Production 13(3):185-190 (2011)